Bardet-Biedl Syndrome Caused by Skipping of SCLT1 Complicated by Microvesicular Steatohepatitis - Horiuchi, Kentaro (Intern Med, 2020)
We treated the case of a 22-year-old male patient with liver dysfunction. At 1 year of age, hepatic fibrosis was suspected. In addition, due to the presence of retinitis pigmentosa, renal failure, obesity, mental retardation, and hypogonadism, he was diagnosed with Bardet-Biedl syndrome (BBS). Skipping of exons 14 and 17 in the sodium channel and clathrin linker 1 (SCLT1) gene was observed. At 22 years of age, the liver enzyme levels were further elevated and a diagnosis of microvesicular steatohepatitis was made. Insulin resistance, a reduction of muscle mass, an impairment of the fatty acid metabolism, and hyperleptinemia in this syndrome may cause steatohepatitis.